The logic of leverage: Reflections on post-foundational political economy - Martijn Konings (Finance and Society, 2018)
This rejoinder takes up some of the points that have been raised by the reviews of Capital and Time in this forum. It engages the question of how political economy should position itself vis-à-vis concerns about the dangers of essentialism and teleological explanation. It argues that a proper theorization of the logic of 'leverage' is key to the development of a political economy that appropriates the insights of post-foundational theory but is still able to account for the reality of power and inequality.
Keywords: 300